Drought events determine performance of Quercus ilex seedlings and increase their susceptibility to Phytophthora cinnamomi (Agricultural and Forest Meteorology, 2014)
More frequent weather extremes are expected to occur in the Mediterranean region within the present context of climate change. These extremes could affect forests and plant diseases driven by pathogens. It is hypothesised that simulation of weather extremes during Quercus ilex growth will influence early performance and susceptibility to the invasive oomycete Phytophthora cinnamomi. In 2010, 140 Q. ilex seedlings were subjected to three watering regimes under greenhouse conditions: waterlogging (W), water stress (S) and optimal watering regime for growth (C). During the second vegetative period, conditions were altered to create the following scenarios: WW, WS, SS, SW and CC. After the second vegetative period, plants were artificially infested with P. cinnamomi. Holm oak (Q. ilex) was more sensitive to flooding in the first year of growth than in the second year. The altered scenarios produced plants with a lower fine-to-total root ratio than plants in unaltered scenarios. Plants with the highest growth rates maintained their relatively rapid growth and photosynthetic activity under altered scenarios. However, plants with the highest growth rates became the plants with the lowest growth rates when two consecutive years of drought occurred, indicating a trade-off by Q. ilex in growth investment, observed only if the water stress scenario persists. Seedlings were more sensitive to water shortage than to waterlogging, especially if they encountered a dry scenario during the first year. Exposure to drought events increased seedling mortality rates after P. cinnamomi infection. Waterlogging combined with subsequent water deprivation was the worst scenario when soil was infested with P. cinnamomi, causing 100% mortality of plants.

Ectomycorrhizal symbiosis in declining and non-declining Quercus ilex trees infected with or free of Phytophthora cinnamomi (Forest Ecology and Management, 2014)
Quercus ilex decline and the presence of the soil-borne pathogen Phytophthora cinnamomi are hypothesised to be associated with shifts in ectomycorrhizal fungi abundance. Soil properties may also influence the relation of this pathogen to ectomycorrhizae. To investigate these associations, 96 Q. ilex declining stands were selected in western Spain and both declining and non-declining trees were sampled. Soil properties (soil depth, Ah horizon thickness, texture, pH, redox potential, soil bulk density and N–NH4+ and N–NO3− concentrations), P. cinnamomi root infections and ectomycorrhizal fungi abundance were assessed. The most dominant ectomycorrhizal morphotypes were Cenococcum geophilum, Tomentella spp. and Russula spp. Lower percentages of non-vital and vital ectomycorrhizal root tips were observed in declining than in non-declining trees. No significant differences in parameters characterising the ectomycorrhizal community between trees infected with or free of P. cinnamomi were observed. However, results indicate that non-mycorrhizal root tips are vulnerable entry points for the pathogen into the tree. More tips were colonised by Russula spp. and other ectomycorrhizal fungi in non-declining infected trees than in declining infected trees. Trees growing on stream banks showed a lower abundance of ectomycorrhizal root tips in fine-textured soils than in coarse-textured soils. Ectomycorrhizal tip abundance was positively related to Ah horizon thickness, irrespective of tree health status. The presence of P. cinnamomi altered relations between ectomycorrhizal abundance and several soil properties. The limited ectomycorrhizal diversity in Q. ilex declining stands and interactions of ectomycorrhizal abundance with soil texture, topography and P. cinnamomi root infections are reported and discussed.

Resource manipulation reveals flexible allocation rules to growth and reproduction in a Mediterranean evergreen oak (JOURNAL OF PLANT ECOLOGY, 2014)
Aims In plants, resource allocation to growth and reproduction may depart from trade-off expectations if (i) investment in growth and reproduction relies on different resource pools, (ii) allocation to reproduction is dependent upon reaching some growth threshold or (iii) reproduction is developmentally linked to growth, both functions relying on the same resource pool. We examined the effects of enhanced resource level on patterns of resource allocation to growth and reproduction in holm oak (Quercus ilex sbsp. ballota), a Mediterranean evergreen tree. Methods In the experimental year (2003), we manipulated the amount of soil nutrients in autumn (to increase nutrient uptake during shoot elongation in the following spring) and soil water in summer (to increase water uptake during acorn growth). Indicators of growth and male and female reproduction were estimated in the pre-experimental (2002), experimental (2003) and post-experimental (2004) years. Important Findings Fertilized trees produced significantly longer shoots, but the number of female flowers per shoot was not affected by treatments. The production of male catkins was also enhanced by fertilization. Irrigation did not affect the production of female flowers or abortion rates. Growth and female reproduction showed no consistent relationship in untreated trees, but resource addition elicited a growth-female reproduction trade-off in the experimental year. The sign of this significant relationship changed in the post-experimental year, indicating the existence of lagged effects of resource manipulation on acorn production. Overall, patterns of allocation to growth and reproduction varied as a function of sex, resource availability and year, a result consistent with extreme allocational plasticity in holm oak.

Combined effects of soil properties and Phytophthora cinnamomi infections on Quercus ilex decline - Corcobado, Tamara; Solla, Alejandro; Madeira, Manuel A.; Moreno, Gerardo (PLANT AND SOIL, 2013)
The importance of soil properties as determinants of tree vitality and Phytophthora cinnamomi root infections was analysed. The study comprised 96 declining stands in western Spain, where declining and non-declining holm oak (Quercus ilex L.) trees were sampled. Soil properties (soil depth, Ah horizon thickness, texture, pH, redox potential, soil bulk density and N-NH4 (+) and N-NO3 (-) concentrations) and P. cinnamomi infections were assessed. Tree mortality rates increased with low soil bulk densities, which were also associated with more P. cinnamomi-infected trees. Occurrence of infected trees was higher in fine textured soils and in thick Ah horizons. Fine textured soils favoured trees, but with the presence of P. cinnamomi their health status deteriorated. Soil under declining trees had higher N-NO3 (-)/N-NH4 (+) ratio values than under non-declining trees. Additional soil properties changes associated to grazing were not related to decline and P. cinnamomi infections. The implications of P. cinnamomi in holm oak decline and the influence of soil properties as contributors to pathogen activity were demonstrated. Fine soil textures and thick Ah horizons, usually favourable for vigour and vitality of trees growing in the Mediterranean climate, were shown to be disadvantageous soil properties if P. cinnamomi was present. Fine soil textures and thick Ah horizons are frequently related with higher levels of soil moisture, which increase the inoculum of the pathogen and favours root infection. Grazing does not seem to be directly linked to Q. ilex health status or P. cinnamomi root rot.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: Nitrogen deposition; Oak decline; Root-rot disease; Silvopastoral systems; Soil compaction; soil texture

A meta-analysis reveals mostly neutral influence of scattered trees on pasture yield along with some contrasted effects depending on functional groups and rainfall conditions (Agriculture, Ecosystems & Environment, 2013)
Scattered trees occurring throughout farmland matrix are prominent features of many human-dominated landscapes around the world, especially in livestock grazing systems. They are keystone structures that may play important roles in maintaining ecosystem functions, services, and farmland biodiversity. However, scattered trees in agricultural landscapes are declining worldwide due to intensive land use. They are often perceived by farmers as having negative impacts on agricultural production. Large-scale assessments in different biomes of agricultural yield in scattered tree ecosystems remain rare. Filling this knowledge gap may help improve decision-making regarding the value of scattered trees in agricultural landscapes. Using meta-analysis, we found that, across four tree functional groups (deciduous, Eucalyptus, N2-fixing, evergreen oak), mature scattered trees do not compromise pasture yield. The sign and magnitude of scattered tree effects on pasture yield did vary, however, among tree functional groups and according to precipitation levels. Our study suggests that, as drought pressure increases abiotic stress, tree facilitation by N2-fixing trees, and competition by Eucalyptus, will become the more common interactions between scattered trees and pasture. Management options exist to conserve and restore scattered trees in agricultural landscapes, but new policies are required to support their widespread adoption by farmers.

Quercus ilex forests are influenced by annual variations in water table, soil water deficit and fine root loss caused by Phytophthora cinnamomi - Corcobado, Tamara; Cubera, Elena; Moreno, Gerardo; Solla, Alejandro (Agricultural and Forest Meteorology, 2013)
Itishypothesised thatmajor reductions intree vitality are related tomarked changes insoilwater content, extremely wet winters followed by dry summers, and the presence of pathogenic organisms which take advantage of this situation. This study helps clarify the role of annual variations in water table, soil water content and ﬁne root abundance in the decline of Quercus ilex forests, with special focus on trees growing in Phytophthora cinnamomi-infested soils. Conducted in western Spain, the study included 5 Q. ilex dehesa stands in which tree water status and soil water dynamic were compared in declining and non-declining trees, and 96 additional stands in which ﬁne root abundance and pathogen assessment were compared in declining and non-declining trees. Declining trees showed signiﬁcantly lower values than non-declining trees for leaf water potential and stomatal conductance. The period of waterlogging (2 months maximum, ﬂuctuating from −0.5 to −4.5m), the soil water content values observed in summer (signiﬁcantly higher in declining trees) and the similar presence of Pythium spiculum in declining and non-declining trees are not sufﬁcient in themselves to explain tree health status. However, ﬁne root density was 16.2% lower in declining than non-declining trees and 42% lower in P. cinnamomi-infected than non-infected trees. Root damage caused by P. cinnamomi in combination with periods of saturated soils favourable for the pathogen but unfavourable for the tree, coupled with small-scale differences in soil water-holding capacity, explain the symptoms and water status of declining trees. The combination of root damage and water stress explained above-ground symptoms of declining trees and will probably determine tree survival.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Oak decline; Open woodlands; Root density; Root-rot disease; Saturated soil; Water deﬁcit

Facilitation of holm oak recruitment through two contrasted shrubs species in Mediterranean grazed woodlands (Journal of Vegetation Science, 2012)
Question: Regeneration failure and gradual tree dieback are major threats for the persistence of savanna-like grazed oak woodlands. Current research has argued that the scarcity of ‘safe sites’, in particular shrubs, is the main cause of the lack of effective tree recruitment. But can different shrub species be considered as safe sites generally? Do two distinct shrub species, with contrasted life strategies, affect several life stages of tree regeneration in similar ways or do they speciﬁcally inﬂuence the recruitment process? Location: Holm oak woodlands of SW Iberian Peninsula (40°02′ N, 06°06′ W). Methods: We surveyed densities of recently emerged and surviving seedlings as well as small and large saplings over two consecutive years in 40 sites that were independently managed, comparing plots encroached by either Cistus ladanifer (a shallow-rooted shrub, forming dense populations, with reported allelopathic compounds) or Retama sphaerocarpa (a N2-ﬁxing, deep-rooted shrub that forms scattered populations) vs their respective control plots (without shrubs). To assess the effect of mature trees and both shrub species on the performance and survival of recently emerged oak seedlings, we established an acorn sowing experiment in the same surveyed microhabitats (open spaces, shrub, tree and tree–shrub). Results: The survey showed that both shrubs species had a positive effect at early recruitment stages. At later life stages, this effect weakened under Cistus whereas it strengthened under Retama. The acorn sowing experiment showed that both shrub species buffered abiotic conditions and enhanced seedling functioning similarly, but Retama enhanced seedling survival to a higher extent than Cistus. Conclusions: The two shrub species impose a speciﬁc template that is able to affect the long-term dynamics of Mediterranean oak woodlands. Cistus shrubs are effective in protecting seedlings physically against herbivores and facilitate early survival, but may compete with older stages of oak regeneration. In contrast, Retama shrubs exert stronger biological facilitation and guarantee longterm persistence of surviving seedlings. We argue that improved understanding of the effectiveness of different nurse plants and their contrasting factors is of major interest for the conservation and restoration of degraded oak woodlands

Root system of Quercus suber L. seedlings in response to herbaceous competition and different watering and fertilisation regimes - Cubera, Elena; Moreno, Gerardo; Solla, Alejandro; Madeira, Manuel (Agroforestry Systems, 2012)
Different management practices are commonly applied to increase pasture yield of Mediterranean open woodlands, but the consequences of increasing competition for soil resources with these practices on tree recruitment are still unknown. In a greenhouse study, belowground competition of Quercus suber L. seedlings growing together with natural (OakNP) or improved pasture (OakIP) was evaluated, and their root systems compared with those of seedlings growing in bare soil (OakBS). Two watering levels and two regimes of P2O5 fertilisation were also tested. Because of competition, the OakIP seedlings had their ﬁne root mass density, coarse root length, and shoot mass reduced by up to 40, 36, and 39%, respectively, when compared to OakNP seedlings. OakNP and OakBS seedlings showed similar average root density parameters and shoot mass values, indicating that Q. suber seedlings growing with natural pasture is a low competitive system. High availability of water and phosphorus did not mitigate the strength of competition between herbaceous plants and oak seedlings, and favoured the pasture to the detriment of the trees. Our ﬁndings suggest that P2O5 fertilisation and irrigation practices performed to improve herbaceous productivity will negatively inﬂuence recruitment of Q. suber seedlings.
Keywords: Cork oak; Dehesa; Improved pasture; Root density; Seedling recruitment

Belowground competition for nutrients in shrub-encroached Mediterranean dehesas (Nutrient Cycling in Agroecosystems, 2011)
Managing multilayered silvopastoral systems such as Mediterranean dehesas requires the study of nutrient resource partitioning among coexisting species and determination to what extent soil nutrients are limiting plant growth. We determined the effects of NPK fertilisation maintained over two consecutive years on dry matter production and nutritional status of pasture (herbaceous) species, two shrub species and Quercus ilex L. in two silvopastoral sites with different shrub-layer species. We selected two prominent Mediterranean shrub species that vary in their speciﬁc ecological strategies: a N2-ﬁxing and sparse deep-rooting shrub (Retama sphaerocarpa (L.) Boiss, Retama site), and a dense shallow-rooting shrub (Cistus ladanifer L., Cistus site). Fertilisation signiﬁcantly (P B 0.05) increased pasture dry mass by 460% and 1,090% in the Retama and Cistus sites, respectively. Nitrogen uptake by pasture species was most stimulated in both sites, and was the major limiting nutrient for this group. At the Cistus site, fertilisation signiﬁcantly increased leaf dry mass of Q. ilex by 53%, but no signiﬁcant effect was found at the Retama site. There were no signiﬁcant effects of fertilisation treatments on dry mass and nutrient status of Retama cladodes and Cistus leaves. Vector analysis revealed that the magnitude of relative changes in nutrient uptake and dry matter production of pasture in response to fertilisation was markedly higher than that of Q. ilex, R. sphaerocarpa and C. ladanifer, suggesting high competitive ability of pasture species for soil nutrients. Results suggest that patterns of soil nutrient partitioning are site-speciﬁc and, thus, likely depend on the dominant species in the shrub layer

Shrub encroachment in Mediterranean silvopastoral systems: Retama sphaerocarpa and Cistus ladanifer induce contrasting effects on pasture and Quercus ilex production (Agriculture, Ecosystems & Environment, 2011)
Silvopastoral systems are threatened worldwide by progressive loss of either tree cover or herbaceous cover due to lack of tree regeneration and shrub encroachment, respectively. Grazed Mediterranean open woodlands, as Iberian dehesa, are an outstanding example of silvopastoral system where shrub encroachment has been proposed as an effective means to facilitate tree seedling recruitment and ensure the system persistence. Shrubs also may interact with pasture understorey and tree overstorey, thereby affecting the overall system productivity. We tested the effects of shrub encroachment on pasture yield, tree growth and acorn production in years of contrasting rainfall in Quercus ilex L. dehesas of centralwestern Spain.We compared the effects oftwo prominentMediterranean shrub species that differ in their ecological strategies: a N2-ﬁxing and sparse deep-rooting shrub (Retama sphaerocarpa (L.) Boiss), and a dense shallow-rooting shrub (Cistus ladanifer L). In intermediate and dry years, pasture yield beneath tree canopy was lower by 21–35% than in open grassland. Pasture yield beneath tree canopy was not signiﬁcantly affected during the wet year. C. ladanifer encroachment signiﬁcantly reduced pasture yield by 68–98%, tree growth by 17–29%, and acorn yield by 6–44%. In contrast, R. sphaerocarpa signiﬁcantly increased pasture yield by 11–157% and tree growth by 6–13%, but had a neutral effect on acorn yield. Our results suggest that pasture is more sensitive to shrub encroachment and annual rainfall variation than is Q. ilex. The importance of C. ladanifer competition and R. sphaerocarpa facilitation on pasture yield increased in the driest year. We conclude that the sign and intensity of shrub encroachment effects on pasture and tree production in Mediterranean dehesas are species-speciﬁc and depend on temporal variation as a function of climate.

Quercus ilex root growth in response to heterogeneous conditions of soil bulk density and soil NH4-N content (Soil and Tillage Research, 2009)
A greenhouse study examined the effects of heterogeneous conditions of soil bulk density and soil NH4-N content on the growth of holm oak (Quercus ilex L.) seedlings over an 8-month period. Heterogeneity of soil was produced inside 150 cm depth pots, by applying manual compaction or enriching different soil layers with NH4 (vertical heterogeneity) and, by splitting the root system into two columns with differing soil bulk density or NH4 conditions (horizontal heterogeneity). Root distribution patterns were assessed by collecting roots within layers, each 10 cm depth, and by recording both the ﬁne (diameter <2 mm) and the coarse (diameter 2 mm) root biomass. Root systems signiﬁcantly responded to the vertical gradients of soil bulk density, decreasing their maximum depth and showing lower values of ﬁne root densities at the layers with a dry bulk density of 1.62 Mg m3 . The split-root system showed that maximum rooting depth of the axis with a dry bulk density of 1.38 Mg m3 was limited by the reduced rooting depth of the adjacent more compacted axis. Root systems were less dense in the NH4 soil treatment than in the control soil treatment (34 mg dm3 vs. 212 mg dm3 ), even at the lowest rate used (0:1 g NH4 L 1 soil ). This high sensitivity to NH4 conducted to a signiﬁcant decrease of shoot height and root depth (50 and 43%, respectively). The split-root system showed that unfavourable conditions of NH4 content have local consequences on the rooting depth and systemic consequences on the ﬁne root density. The implications of root growth restrictions for Q. ilex natural regeneration, seedling survival, and decline are discussed.

Quercus ilex root growth in response to heterogeneous conditions of soil bulk density and soil NH4-N content - Cubera, Elena; Moreno, Gerardo; Solla, Alejandro (Soil and Tillage Research, 2009)
A greenhouse study examined the effects of heterogeneous conditions of soil bulk density and soil NH4-N content on the growth of holm oak (Quercus ilex L.) seedlings over an 8-month period. Heterogeneity of soil was produced inside 150 cm depth pots, by applying manual compaction or enriching different soil layers with NH4 (vertical heterogeneity) and, by splitting the root system into two columns with differing soil bulk density or NH4 conditions (horizontal heterogeneity). Root distribution patterns were assessed by collecting roots within layers, each 10 cm depth, and by recording both the ﬁne (diameter <2 mm) and the coarse (diameter 2 mm) root biomass. Root systems signiﬁcantly responded to the vertical gradients of soil bulk density, decreasing their maximum depth and showing lower values of ﬁne root densities at the layers with a dry bulk density of 1.62 Mg m3 . The split-root system showed that maximum rooting depth of the axis with a dry bulk density of 1.38 Mg m3 was limited by the reduced rooting depth of the adjacent more compacted axis. Root systems were less dense in the NH4 soil treatment than in the control soil treatment (34 mg dm3 vs. 212 mg dm3 ), even at the lowest rate used (0:1 g NH4 L 1 soil ). This high sensitivity to NH4 conducted to a signiﬁcant decrease of shoot height and root depth (50 and 43%, respectively). The split-root system showed that unfavourable conditions of NH4 content have local consequences on the rooting depth and systemic consequences on the ﬁne root density. The implications of root growth restrictions for Q. ilex natural regeneration, seedling survival, and decline are discussed.
Keywords: Oak decline; Quercus ilex; Root density; Root depth; Soil bulk density; Soil NH4 content

Impact of stand density on water status and leaf gas exchange in Quercus ilex (Forest Ecology and Management, 2008)
Tree thinning reduces tree-to-tree competition and likely contributes to the improvement of tree water status and productivity in water-limited systems. In this study, we examined the importance of competition for water among Quercus ilex trees in open woodlands by comparing the water consumption and physiological status of trees located along stand density gradients which ranged from 10% (low density; LD) to 100% (high density; HD) of canopy cover. The study was carried out at two sites which differed in mean annual rainfall (506 and 816 L m 2 ; Dsite and Wsite , respectively). Predawn and midday leaf water potential (cd and cm, respectively) and CO2 assimilation rate (A) were measured every two weeks from mid May to mid September, in eight trees located along a stand density gradient at each site. Sap ﬂow and soil moisture were measured only at Dsite . Sap ﬂow was continuously recorded by sap ﬂowmeters (constant heating method) installed in 12 trees along two stand density gradients. Soil moisture (U) was measured every 20 cm for the ﬁrst meter and then every 50 cm up to 250 cm. Measurements were conducted in 18 soil proﬁles, 6 located in HD and 12 in LD (six beneath and six out the canopy). At Wsite , differences among stand densities for c and A were very small and emerged only at the end of the dry season. At Dsite , c (both predawn and midday), A, U, and sap ﬂow density were signiﬁcantly higher in LD trees than in HD ones. At Dsite , some water remained unused in the soil at the end of the dry season beyond the canopy in the LD areas, and trees did not experienced such an acute water deﬁcit (cd > 1 MPa) as the HD trees did (cd < 3 MPa). Summer tree transpiration at the stand level (Estand) tended to saturate with the increase of canopy cover. Estand increases by 32% when canopy cover goes from 50% to 100%. Results conﬁrmed that the increase of tree-to-tree competition with stand density was much more signiﬁcant at dry sites. In these sites, tree thinning is recommended as a way to maintain tree functioning

Impact of stand density on water status and leaf gas exchange in Quercus ilex - Moreno, Gerardo; Cubera, Elena (Forest Ecology and Management, 2008)
Tree thinning reduces tree-to-tree competition and likely contributes to the improvement of tree water status and productivity in water-limited systems. In this study, we examined the importance of competition for water among Quercus ilex trees in open woodlands by comparing the water consumption and physiological status of trees located along stand density gradients which ranged from 10% (low density; LD) to 100% (high density; HD) of canopy cover. The study was carried out at two sites which differed in mean annual rainfall (506 and 816 L m 2 ; Dsite and Wsite , respectively). Predawn and midday leaf water potential (cd and cm, respectively) and CO2 assimilation rate (A) were measured every two weeks from mid May to mid September, in eight trees located along a stand density gradient at each site. Sap ﬂow and soil moisture were measured only at Dsite . Sap ﬂow was continuously recorded by sap ﬂowmeters (constant heating method) installed in 12 trees along two stand density gradients. Soil moisture (U) was measured every 20 cm for the ﬁrst meter and then every 50 cm up to 250 cm. Measurements were conducted in 18 soil proﬁles, 6 located in HD and 12 in LD (six beneath and six out the canopy). At Wsite , differences among stand densities for c and A were very small and emerged only at the end of the dry season. At Dsite , c (both predawn and midday), A, U, and sap ﬂow density were signiﬁcantly higher in LD trees than in HD ones. At Dsite , some water remained unused in the soil at the end of the dry season beyond the canopy in the LD areas, and trees did not experienced such an acute water deﬁcit (cd > 1 MPa) as the HD trees did (cd < 3 MPa). Summer tree transpiration at the stand level (Estand) tended to saturate with the increase of canopy cover. Estand increases by 32% when canopy cover goes from 50% to 100%. Results conﬁrmed that the increase of tree-to-tree competition with stand density was much more signiﬁcant at dry sites. In these sites, tree thinning is recommended as a way to maintain tree functioning
Keywords: leaf water potential; open woodland; photosynthesis; sap flow; Soil moisture

Light distribution in scattered-trees open woodlands in Western Spain (Agroforestry Systems, 2008)
We have studied the percentage of radiation transmitted through the tree canopy to the underlying pasture and crops in dehesas of Southwest Spain by means of ﬁsh-eye photographs taken at different distances from the tree. Thirty-six trees were studied covering all the diametric classes (0.1–14 m canopy width) of two stands, with mean density of 19 mature trees ha -1 . Intercepted light decreased with distance following an logistic curve, indicating a rapid increase in the light availability with distance from the tree. For mature trees, radiation was constant beyond 20 m. Applying a multivariable regression light equation, distance, stem diameter and canopy width explained more than 88% of the light variability for each orientation studied. A simple model was built up from light equations, tree growth curves and allometric relationships. From this model, we have estimated that radiation available for crops and pasture decreased up to 21% due to the presence of trees in a standard dehesa with 24 mature trees ha -1 and 13% of canopy cover. In addition, we have generated different radiation maps of virtual dehesas differing in tree age, density and arrangement, which could be useful to determine optimal tree planting schemes and consequent pruning and thinning regimes.

Light distribution in scattered-trees open woodlands in Western Spain - Montero, María Jesús; Moreno, Gerardo; Bertomeu, Manuel (Agroforestry Systems, 2008)
We have studied the percentage of radiation transmitted through the tree canopy to the underlying pasture and crops in dehesas of Southwest Spain by means of ﬁsh-eye photographs taken at different distances from the tree. Thirty-six trees were studied covering all the diametric classes (0.1–14 m canopy width) of two stands, with mean density of 19 mature trees ha -1 . Intercepted light decreased with distance following an logistic curve, indicating a rapid increase in the light availability with distance from the tree. For mature trees, radiation was constant beyond 20 m. Applying a multivariable regression light equation, distance, stem diameter and canopy width explained more than 88% of the light variability for each orientation studied. A simple model was built up from light equations, tree growth curves and allometric relationships. From this model, we have estimated that radiation available for crops and pasture decreased up to 21% due to the presence of trees in a standard dehesa with 24 mature trees ha -1 and 13% of canopy cover. In addition, we have generated different radiation maps of virtual dehesas differing in tree age, density and arrangement, which could be useful to determine optimal tree planting schemes and consequent pruning and thinning regimes.
Keywords: allometric relationships; Dehesa; fish-eye photograph; light transmittance; Quercus ilex; radiation map

Effect of land-use on soil water dynamic in dehesas of Central–Western Spain (Catena, 2007)
Dehesa ecosystems are open woodlands with scattered oak trees as their main component. As a result of differing land-uses, the structure of vegetation found within dehesas varies between: (i) oak trees and intercropped cereals (cropped), (ii) oak trees and native grass vegetation (grazed), and (iii) oak trees with abundant understorey shrubs (encroached). The aim of this study is to investigate whether land-use influences the water dynamics of dehesas by measuring available soil water content (AWC) in the upper 250 cm of the soil at different distances from tree trunks (maximum 30 m) at four Quercus ilex dehesas in Central–Western Spain. The technique used was Time Domain Reflectometry and the study was undertaken between May of 2002 and December of 2005. Leaf water potential (Ψ) was also measured on trees at one site by mean of a pressure chamber. Within the upper meter of the soil, it appears that trees, grasses and shrubs extracted soil water resources in a similar way from both beneath and beyond the tree canopy. However, encroached plots in general showed lower average AWC values than cropped or grazed plots (3.7, 5.6, and 6.2% in encroached, cropped and grazed, respectively). Cereal crops do not compete more strongly than grasses with trees for available soil water resources. The similar Ψ values found at cropped and grazed plots supported these results. From our results, it could be hypothesized that ploughed dehesas could facilitate soil re-watering in the plots with pronounced slopes. The decrease of AWC values at encroached plots with respect to the cropped and grazed plots was found mostly beyond the tree trunk at deeper soil layers, indicating that shrubs use water partly not accessible to trees. The presence of an understory of shrubs seems to have slightly increased the water constraints on trees during the summer period (Ψd values of −0.5, −0.5, and −0.8 MPa in cropped, grazed, and encroached plots, respectively). In cropped and grazed plots, an important amount of water seems to have remained unused for trees and grasses.

Effect of land-use on soil water dynamic in dehesas of Central–Western Spain - Cubera, Elena; Moreno, Gerardo (Catena, 2007)
Dehesa ecosystems are open woodlands with scattered oak trees as their main component. As a result of differing land-uses, the structure of vegetation found within dehesas varies between: (i) oak trees and intercropped cereals (cropped), (ii) oak trees and native grass vegetation (grazed), and (iii) oak trees with abundant understorey shrubs (encroached). The aim of this study is to investigate whether land-use influences the water dynamics of dehesas by measuring available soil water content (AWC) in the upper 250 cm of the soil at different distances from tree trunks (maximum 30 m) at four Quercus ilex dehesas in Central–Western Spain. The technique used was Time Domain Reflectometry and the study was undertaken between May of 2002 and December of 2005. Leaf water potential (Ψ) was also measured on trees at one site by mean of a pressure chamber. Within the upper meter of the soil, it appears that trees, grasses and shrubs extracted soil water resources in a similar way from both beneath and beyond the tree canopy. However, encroached plots in general showed lower average AWC values than cropped or grazed plots (3.7, 5.6, and 6.2% in encroached, cropped and grazed, respectively). Cereal crops do not compete more strongly than grasses with trees for available soil water resources. The similar Ψ values found at cropped and grazed plots supported these results. From our results, it could be hypothesized that ploughed dehesas could facilitate soil re-watering in the plots with pronounced slopes. The decrease of AWC values at encroached plots with respect to the cropped and grazed plots was found mostly beyond the tree trunk at deeper soil layers, indicating that shrubs use water partly not accessible to trees. The presence of an understory of shrubs seems to have slightly increased the water constraints on trees during the summer period (Ψd values of −0.5, −0.5, and −0.8 MPa in cropped, grazed, and encroached plots, respectively). In cropped and grazed plots, an important amount of water seems to have remained unused for trees and grasses.
Keywords: available water content; cultivation; Encroachment; fertilisation; Land-use

Effect of single Quercus ilex trees upon spatial and seasonal changes in soil water content in dehesas of central western Spain - Cubera, Elena; Moreno, Gerardo; Elena, C.; Gerardo, M. (Ann. For. Sci., 2007)
The spatial and temporal evolution of soil water content () in Quercus ilex dehesas has been investigated to determine how trees modify the soil water dynamics and the nature of tree-grass interactions in terms of soil water use in these ecosystems. Soil physical parameters and were measured at different distances from the tree trunk (2-30 m) in the upper 300 cm of soil. was measured monthly by TDR during 2002-2005. Tree water potential was determined during the summers of 2004 and 2005. At deeper soil layers, mean values were higher beyond than beneath tree canopy during dry periods. depletion beyond tree canopy continued even in summer, when herbaceous plants dried up, suggesting that trees uptake water from the whole inter-tree space. Results have shown a high dependence of trees on deep water reserves throughout late spring and summer, which helps to avoid competition for water with herbaceous vegetation.
Keywords: Oak woodland; Quercus ilex; Soil water content; TDR; tree-grass interaction

Effect of single Quercus ilex trees upon spatial and seasonal changes in soil water content in dehesas of central western Spain (Ann. For. Sci., 2007)
The spatial and temporal evolution of soil water content () in Quercus ilex dehesas has been investigated to determine how trees modify the soil water dynamics and the nature of tree-grass interactions in terms of soil water use in these ecosystems. Soil physical parameters and were measured at different distances from the tree trunk (2-30 m) in the upper 300 cm of soil. was measured monthly by TDR during 2002-2005. Tree water potential was determined during the summers of 2004 and 2005. At deeper soil layers, mean values were higher beyond than beneath tree canopy during dry periods. depletion beyond tree canopy continued even in summer, when herbaceous plants dried up, suggesting that trees uptake water from the whole inter-tree space. Results have shown a high dependence of trees on deep water reserves throughout late spring and summer, which helps to avoid competition for water with herbaceous vegetation.

Effects of trees and understorey management on soil fertility and nutritional status of holm oaks in Spanish dehesas (Nutrient Cycling in Agroecosystems, 2007)
A dehesa is a multipurpose agroforestry system with scattered oaks. This study focuses on the inﬂuence of trees on soil chemical fertility and on the consequences of dehesa land use for soil fertility and nutritional status of trees. To achieve that we have studied the content of several nutrients in soils and tree leaves in four Spanish dehesas, considering three types of land use: scattered holm oak with an understorey of either native grasses (G), shrubs (E) or crop (C: either fertilized or unfertilized). We randomly selected six oaks per farm and land use for soil and tree leaf sampling. Soil samples were taken at ﬁve distances from each tree trunk (2, 5, 10, 15, and 20 m) at a depth of 0–30 cm. SOM, CEC, total and mineral-N, available-P, and exchangeable Ca, Mg and K were analysed. Foliar samples were collected from every tree in two consecutive years (2002 and 2003) at leaf maturity. The total content of N, P, K, Ca, and Mg was determined. Soils of C plots showed signiﬁcantly higher contents for most of the nutrients studied than G ones. Cropping also affected trees positively, with higher foliar contents of N and K in C plots than in G ones. Foliar content did not decrease for any nutrient, and tree-crop interaction is interpreted as a mechanism of complementarity in terms of nutrient use. Shrub encroachment led to a higher content of organic-N and exchangeable cations in soils, but to a decrease in mineral N and available-P. The tree foliar contents of N, Mg, and Ca were lower in E plots than in G plots, probably as a consequence of the tree-shrub competition for those nutrients. By contrast, P content of tree leaves increased signiﬁcantly in E plots compared to G plots.